2013
DOI: 10.1177/1541931213571421
|View full text |Cite
|
Sign up to set email alerts
|

A Driving Simulation Study Examining Destination Entry with iOS 5 Google Maps and a Garmin Portable GPS System

Abstract: A simulation study compared 23 young adult drivers' task completion time, mean glance time, number of glances, and percentage of long glances while performing a navigation entry task with a Garmin portable GPS system and a mobile navigation application (iOS 5 Google Maps) on an iPod Touch. We compared participants' performance on these tasks using the National Highway Traffic Safety Administration (NHTSA) eye-glance acceptance criteria. We found that, irrespective of the device used, no participant was able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Workload is best defined by the person doing the task and may involve mental effort , the amount of attention required, physical effort, time pressure, distraction, or frustration associated with trying to do the task while continuing to drive safely’. Previous work (Beckers et al 2014 ; Dopart et al 2013 ) using this approach produced ratings across user interface tasks that were consistent with relative rankings obtained concurrently using the NASA-Task Load Index (Hart 2006 ; Hart and Staveland 1988 ), one of the most widely used subjective workload assessment scales. In this regard, Hendy, Hamilton, and Landry ( 1993 ) provide a useful consideration of the sensitivity of simple univariate workload scales relative to multifactor scales when the goal is to obtain an overall workload rating.…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…Workload is best defined by the person doing the task and may involve mental effort , the amount of attention required, physical effort, time pressure, distraction, or frustration associated with trying to do the task while continuing to drive safely’. Previous work (Beckers et al 2014 ; Dopart et al 2013 ) using this approach produced ratings across user interface tasks that were consistent with relative rankings obtained concurrently using the NASA-Task Load Index (Hart 2006 ; Hart and Staveland 1988 ), one of the most widely used subjective workload assessment scales. In this regard, Hendy, Hamilton, and Landry ( 1993 ) provide a useful consideration of the sensitivity of simple univariate workload scales relative to multifactor scales when the goal is to obtain an overall workload rating.…”
Section: Methodssupporting
confidence: 64%
“…While the values obtained with each method differ and are worthy of consideration (e.g. Dopart et al 2013 ; Reimer et al 2013 ), using one or the other did not appreciably change the relative pattern of results in this data set comparing systems and modalities. Given the potential relevance to ongoing guideline development, the metrics recommended by NHTSA are presented.…”
Section: Methodsmentioning
confidence: 69%
“…The 85 th percentile of the mean OTs for the NHTSA scenario was exactly 2.0 seconds. However, when looking at our test results, the results of [4], and the Wierwille's visual sampling model for real driving [17], this acceptance criteria does not make much sense. The average in-car glance durations for the test tasks were all below 1.0 seconds and in line with Wierwille's model.…”
Section: Discussionmentioning
confidence: 98%
“…These could be due to personal factors such as uncertainty toleration [4] or the skill level of the driver [18]. The usage of the often-used 85 th percentile in the acceptance criteria shows a pretty nice sense of realism about the data.…”
Section: Discussionmentioning
confidence: 99%
“…Driver interactions with smartphones are generally complex, placing considerable attention on the safety concerns of use while driving. Research has shown that different types of devices have differential draws on driver attention [7,2]. Other work investigating the modality of interactions suggests that voice interfaces may be less demanding than visual-manual equivalents [3,8].…”
Section: Introductionmentioning
confidence: 99%